The concept of caring in nursing: results from a pilot research study - Patiraki, Elisabeth; Efstathiou, George; Nikitara, Monica; Tsangari, Haritini; Merkouris, Anastasios; Karlou, Chrysoula; Palese, Alvisa; Tomietto, Marco; Balogh, Zoltan; Suhonen, Riitta; Leino-Kilpi, Helena; Jarosova, Darja; et al. (My University, 2010)
Background: International literature identifies many gaps in the concept of caring. Investigation is needed in order to understand how nurses and patients perceive caring. Aim: To examine and compare the concept of caring and individualized caring as perceived by patients and nurses, and to assess the levels of patient satisfaction with nursing care in 6 European countries. Method: In this study, which was the pilot phase of a larger project, 369 persons participated, 182 nurses and 187 patients, recruited by the convenience sampling process, in 6 European countries, Cyprus, Greece, Finland, Hungary, Italy and the Czech Republic. The response rate was 78.11% for nurses and 83.11% for patients. Data were collected from surgical units during May 2009. For the purpose of this study, three instruments were used: (a) the Caring Behaviors Inventory (CBI) which measures the frequency of the provided caring as perceived by both nurses and patients, (b) the Individualized Care Scale (ICS) which examines the support and provision of individualized care in two dimensions, ICS-A support, ICS-B provision, and (c) the Patient Satisfaction Scale (PSS) which examines the patients' satisfaction with the nursing care received. Descriptive statistics, t-test, chi-square and ANOVA were performed for analysis of the responses. The level of statistical significance was set at p<0.05. Results: Statistically significant difference between the views of patients and nurses was observed only for ICS-A (p=0.001), with nurses scoring higher than patients. The concept of individualized care was not supported by the nurses, although they reported that they offered it to the patients. The patients' satisfaction with the nursing care they received was reported high. Satisfaction with nursing care was significantly correlated with the frequency of the provision of nursing care (r=0.764, p<0.001), with the support of the idea of individualized care (r=0.674, p<0.001), and with receipt of individualized care (r=0.701, p<0.001). Conclusions: The study findings partially support reports in the relevant literature of differences between the perceptions of nurses and patients about care, general and individualised. They fully support previous findings that nursing caring behavior is highly correlated with patient satisfaction. The lack of such studies at the European and international level demonstrates the need for further analysis of this concept using larger samples.
Keywords: Caring; Individualized nursing care; Patient satisfaction